The impact of the COVID-19 pandemic on the performance and risk profile of airline stocks - Huan H. Nguyen; Truc Thi Nha Phan; Vu Minh Ngo (Contemporary Economics, 2022)
The COVID-19 outbreak dealt a severe blow to the global economy, especially to the airline industry, due to worldwide lockdown measures implemented by the authorities. This paper aims to investigate the impact of the COVID-19 pandemic on the airline stock performance of seven markets in Asia and three other markets in Australia, Germany and the United States. The data is collected from 42 airline firms from 2019 to 2020. The research outcomes indicate that: (a) COVID-19 only temporarily impacts stock returns; (b) Market values plunge immediately after the first confirmed case, and it still shows no evidence of returning to the price levels before the outbreak; (c) COVID-19 has a significant impact on stock volatility; (d) Most stocks do not illustrate any higher exposure to systematic risks.
Keywords: G14; G15; L93; 330; COVID-19; pandemic; airline stock return; risk performance